The thioredoxin‐1 inhibitor Txnip restrains effector T‐cell and germinal center B‐cell expansion. Issue 1 (28th September 2020) - Muri, Jonathan; Thut, Helen; Kopf, Manfred
Abstract: Thioredoxin‐1 (Trx1) is a vital component for cellular redox homeostasis. In T cells, Trx1 donates electrons for the de novo synthesis of deoxyribonucleotides to allow rapid cell proliferation. The Trx‐interacting protein (Txnip) binds to the reduced Trx1 and inhibits its activity. However, the role of Txnip in adaptive immunity in vivo is unknown. Here, we show that absence of Txnip increased proliferation of effector T cells and GC B‐cell responses in response to lymphocytic choriomeningitis virus and Qβ virus‐like particles, respectively, but did not affect development and homeostasis of T and B cells. While downregulation of Txnip and concomitant upregulation of Trx1 is critical for rapid T‐cell expansion upon viral infection, re‐expression of Txnip and consequently inhibition of Trx1 is important to restrain late T‐cell expansion. Importantly, we demonstrated that T‐cell receptor (TCR) engagement but not CD28 costimulation is critically required for Txnip downregulation. Thus, this study further uncovers positive and negative control of lymphocyte proliferation by the Trx1 system. Abstract : We found that the thioredoxin (Trx)‐interacting protein (Txnip), the inhibitor of the Trx1 system, restrains proliferation of effector T cells and GC B cells in immune responses but does not affect their development and homeostasis. This finding may be exploited to fine tune lymphocyte responses in vivo.